Energy Transfer: Nearly 100% Triplet Harvesting in Conventional Fluorescent Dopant‐Based Organic Light‐Emitting Devices Through Energy Transfer from Exciplex (Adv. Mater. 12/2015). (March 2015) - Liu, Xiao‐Ke; Chen, Zhan; Zheng, Cai‐Jun; Chen, Miao; Liu, Wei; Zhang, Xiao‐Hong; Lee, Chun‐Sing
Abstract : On page 2025, C.‐J. Zheng, X.‐H. Zhang, C.‐S. Lee, and co‐workers report a conventional fluorescent‐dopant‐based organic light‐emitting device (OLED) with an external quantum efficiency as high as 14.5%, close to nearly 100% triplet harvesting, through energy transfer from the exciplex. This device concept represents a simple and fruitful approach for getting high‐efficiency, low‐operating‐voltage OLEDs with good color purities.